2022
DOI: 10.1186/s40635-022-00482-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular pressure reactivity and brain tissue oxygen monitoring provide complementary information regarding the lower and upper limits of cerebral blood flow control in traumatic brain injury: a CAnadian High Resolution-TBI (CAHR-TBI) cohort study

Abstract: Background Brain tissue oxygen tension (PbtO2) and cerebrovascular pressure reactivity monitoring have emerged as potential modalities to individualize care in moderate and severe traumatic brain injury (TBI). The relationship between these modalities has had limited exploration. The aim of this study was to examine the relationship between PbtO2 and cerebral perfusion pressure (CPP) and how this relationship is modified by the state of cerebrovascular pressure reactivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…A key takeaway from this study is that rSO 2 as a raw absolute parameter provides little, if any prognostic value in the ICU. This is consistent with recent studies that found high-resolution rSO 2 signals to have differing statistical properties to more established monitoring modalities in moderate-to-severe TBI including brain tissue oxygenation (PbtO 2 ), CPP, and ICP, as well as various measures of CVR [ 47 , 48 ]. It should be noted that in alternative settings, such as intraoperative monitoring, change in rSO 2 is viewed as a more reliable metric of cerebral hypoxia and ischemic risk [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…A key takeaway from this study is that rSO 2 as a raw absolute parameter provides little, if any prognostic value in the ICU. This is consistent with recent studies that found high-resolution rSO 2 signals to have differing statistical properties to more established monitoring modalities in moderate-to-severe TBI including brain tissue oxygenation (PbtO 2 ), CPP, and ICP, as well as various measures of CVR [ 47 , 48 ]. It should be noted that in alternative settings, such as intraoperative monitoring, change in rSO 2 is viewed as a more reliable metric of cerebral hypoxia and ischemic risk [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although ICP either did not change or decrease in this group, we attributed PbtO 2 deterioration to MAP augmentation. Further, MAP augmentation, when Pa co 2 increases and cerebral autoregulation is impaired, may increase ICP and decrease PbtO 2 (11). Among PbtO 2 responder group 3, where baseline PbtO 2 was low and improved to a normal threshold, one MAP challenge test resulted in ICP increasing from 15 mm Hg to 20 mm Hg when cerebral autoregulation was impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The important knowledge is the identification of factors that affect CBF, such as CPP, autoregulation status, and arterial partial pressure of oxygen and carbon dioxide. To prevent sequelae of elevated ICP (herniation syndrome such as uncal ,central transtentorial, subfalcine and tonsillar herniation and cerebral ischemia and hypoxia comprised decreased in CPP and brain oxygen delivery) is to perform neuro-monitoring that classified into monitor in driving pressure (ICP and CPP), CBF (Transcranial Doppler (TCD) ultrasound for detect local and regional blood flow), brain oxygen delivery (Jugular venous oxygen satura- tion (Sjvo 2 ), Near-infrared spectroscopy (NIRS) and Brain tissue oxygenation (PbtO 2 ), cerebral metabolism (CMD to measure cerebral lactate-pyruvate ratio, cerebral lactate and glucose) and central nervous system function (EEG and electrophysiology study) that recommend threshold level in Table 4 [6][7][8][9][10][11]24] and the diagram of the neuromonitoring strategy in traumatic brain injury in Figure 2.…”
Section: Neuromonitoring In Traumatic Brain Injurymentioning
confidence: 99%
“…CeOx has been cleared by the United States Food and Drug Administration for monitoring regional cerebral oxygen saturation [4], and cerebral deoxygenation (rSO 2 below 55%) has been shown to correlate with a variety of adverse systemic complications and multi-organ failure, for example, renal failure, overall well-being, prolonged ventilation, cortical dysfunction, cerebral hypoxia, and low cardiac output syndromes. Many studies [1,7,12,16] showed that CeOx with NIRS correlated with CPP estimation, the Glasgow Outcome Score Scale, and mortality in patients with severe TBI, and NIRS has the capability to provide an early warning of cerebral ischemia and infarction. These impacts of continuous monitoring showed the above correlations between regional cerebral saturation and systemic outcomes, and most of the intraoperative measures taken to optimize cerebral rSO 2 and oxygen delivery potentially affect systemic perfusion (e.g., alterations in PaCO 2 , cardiac output, arterial blood pressure, etc.).…”
Section: Neuromonitoring In Traumatic Brain Injurymentioning
confidence: 99%